Complex evolution of a Y-chromosomal double homeobox 4 (DUX4)-related gene family in hominoids. - Julia Schmidt (PLoS ONE, 2009)
The human Y chromosome carries four human Y-chromosomal euchromatin/heterochromatin transition regions, all of which are characterized by the presence of interchromosomal segmental duplications. The Yq11.1/Yq11.21 transition region harbours a peculiar segment composed of an imperfectly organized tandem-repeat structure encoding four members of the double homeobox (DUX) gene family. By comparative fluorescence in situ hybridization (FISH) analysis we have documented the primary appearance of Y-chromosomal DUX genes (DUXY) on the gibbon Y chromosome. The major amplification and dispersal of DUXY paralogs occurred after the gibbon and hominid lineages had diverged. Orthologous DUXY loci of human and chimpanzee show a highly similar structural organization. Sequence alignment survey, phylogenetic reconstruction and recombination detection analyses of human and chimpanzee DUXY genes revealed the existence of all copies in a common ancestor. Comparative analysis of the circumjacent beta-satellites indicated that DUXY genes and beta-satellites evolved in concert. However, evolutionary forces acting on DUXY genes may have induced amino acid sequence differences in the orthologous chimpanzee and human DUXY open reading frames (ORFs). The acquisition of complete ORFs in human copies might relate to evolutionary advantageous functions indicating neo-functionalization. We propose an evolutionary scenario in which an ancestral tandem array DUX gene cassette transposed to the hominoid Y chromosome followed by lineage-specific chromosomal rearrangements paved the way for a species-specific evolution of the Y-chromosomal members of a large highly diverged homeobox gene family.